Cell-free DNA diagnostics: current and emerging applications in oncology. (15th April 2019) - Muluhngwi, Penn; Valdes Jr, Roland; Fernandez-Botran, Rafael; Burton, Eric; Williams, Brian; Linder, Mark W
Liquid biopsy is a noninvasive dynamic approach for monitoring disease over time. It offers advantages including limited risks of blood sampling, opportunity for more frequent sampling, lower costs and theoretically non-biased sampling compared with tissue biopsy. There is a high degree of concordance between circulating tumor DNA mutations versus primary tumor mutations. Remote sampling of circulating tumor DNA can serve as viable option in clinical diagnostics. Here, we discuss the progress toward broad adoption of liquid biopsy as a diagnostic tool and discuss knowledge gaps that remain to be addressed.